The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/cncr.23279
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node‐positive head and neck cancer treated with definitive radiotherapy

Abstract: We investigated the prognostic impact of absolute lymphocyte count (ALC) following induction chemotherapy in newly diagnosed adult acute lymphoblastic leukemia (ALL). Patients with ALC ≥350 cells/μL at day 28 had a median overall survival (OS) of 47.4 months when compared with 17.6 months for those with an ALC <350 cells/μL (HR = 1.98, P = 0.007). Among patients who achieved a complete remission, median event‐free survival (EFS) for those with ALC ≥350 cells/μL on day 28 was 42.1 months when compared with 13.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 27 publications
(29 reference statements)
0
16
1
Order By: Relevance
“…While numerous studies have proposed CT-based criteria to help guide post-RT neck evaluation and management [8, 10, 23, 24], refining such criteria is not the intent of this study, as all patients in our cohort achieved disease control with RT-based treatments alone. We believe the value of the current study is to further develop our understanding of nodal regression in HPV-associated OPCs.…”
Section: Discussionmentioning
confidence: 99%
“…While numerous studies have proposed CT-based criteria to help guide post-RT neck evaluation and management [8, 10, 23, 24], refining such criteria is not the intent of this study, as all patients in our cohort achieved disease control with RT-based treatments alone. We believe the value of the current study is to further develop our understanding of nodal regression in HPV-associated OPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Yeung et al[14] documented that the risk of leaving disease in the neck if the ND is limited to the levels of residual adenopathy is only 5%. Taking this into account, if residual adenopathy is on a single level and the dissection encompasses that particular level and 1 or 2 levels distally, the expected risk of leaving behind the disease would be much lower than 5%.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of organ preservation protocols that have soared in recent years, planned ND has become less apparent and the concept of salvage ND comes into the picture. Over the past few years, multiple studies have been conducted on the role of a more targeted surgery of a selective or limited ND after primary CRT [11-14]. Recent data suggest that a more conservative approach of ND is adequate to remove metastatic neck disease with minimal morbidities but comparable oncological outcomes [2, 4, 11, 15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that SND, more than its timing, is associated with lower complications (SND complication <5%) [48]. The use of SND was reported as suitable after CRT also in patients with advanced regional disease.…”
Section: The Timing Of Nd After Crtmentioning
confidence: 99%
“…On the one hand is the risk of neck recurrences or microscopic residual disease, on the other hand is the probability of an overtreatment with possible surgical complications (lymphedema, dysphagia, fistulae) [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72]. Benefits may include local regional control and OS [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,…”
Section: Introduction: Pros and Consmentioning
confidence: 99%